Inflammation‐Stimulated MSC‐Derived Small Extracellular Vesicle miR‐27b‐3p Regulates Macrophages by Targeting CSF‐1 to Promote Temporomandibular Joint Condylar Regeneration. Issue 16 (11th March 2022) - Liu, Yufei; Zhang, Zhiling; Wang, Biao; Dong, Yunsheng; Zhao, Congrui; Zhao, Yanhong; Zhang, Lin; Liu, Xiangsheng; Guo, Jingyue; Chen, Yuehua; Zhou, Jie; Yang, Tingting; et al.
Abstract: Small extracellular vesicles (sEVs) secreted by mesenchymal stem cells (MSCs) have been extensively studied in recent years. sEV contents change with the secreting cell state. When MSCs are exposed to an inflammatory environment, they release more functional growth factors, exosomes, and chemokines. Herein, MSCs are stimulated to alter sEV cargos and functions to regulate the inflammatory microenvironment and promote tissue regeneration. Sequencing of sEV miRNAs shows that certain RNAs conducive to cell function are upregulated. In this study, in vitro cell function experiments show that both inflammation‐stimulated adipose‐derived MSC (ADSC)‐derived sEV (IAE) and normal ADSC‐derived sEV (AE) promote cell proliferation; IAE also significantly improves cell migration. Regarding macrophage polarization regulation, IAE significantly promotes M2 macrophage differentiation. RNA‐sequencing analysis indicates that high miR‐27b‐3p expression levels in IAE may regulate macrophages by targeting macrophage colony‐stimulating factor‐1 (CSF‐1). In vivo, a rabbit temporomandibular joint (TMJ) condylar osteochondral defect model shows that both AE and IAE promote TMJ regeneration, with IAE having the most significant therapeutic effect. Therefore, the authors confirm that exposing MSCs to an inflammatory environment can feasibly enhance sEV functions and that modified sEVs achieve better therapeutic effects. Abstract : Macrophages activated into the M1 phenotype aggravate arthritis. The expression of colony‐stimulating factor‐1 (CSF‐1) in macrophages is inhibited by high expression levels of miR‐27b‐3p in small extracellular vesicles which are derived from inflammation‐stimulated adipose‐derived mesenchymal stem cells (IAE). The downregulation of CSF‐1 leads to reduced inflammation. Furthermore, the growth factors carried by IAE can promote the regeneration of condylar defects.